Estudo das interações parasitos-hospedeiro em morcegos provindos de ambientes urbanos no Rio Grande do Sul, Brasil - Silva, Daniele da (2024)
The present work investigated parasitism in bats from urban areas of 34 municipalities in Rio Grande do Sul. The animals evaluated were obtained from the Instituto de Pesquisas Veterinárias Desidério Finamor, sent by the Centro Estadual de Vigilância em Saúde, to carry out diagnostic tests for bats rabies, during the period from 2016 to 2021. Of the 109 animals surveyed, 35.8% (39/109) had ectoparasites, with an average of 9.9 parasites per animal. A total of 385 ectoparasites were recovered, including Rhipicephalus microplus, Chirnyssoides sp., Ewingana inaequalis and Chiroptonyssus robustipes. Of these bats, all had insectivorous eating habits, 35.9% (14/39) females and 64.1% (25/39) males. Co-parasitism of mites Chirnyssoides sp., Ewingana inaequalis and Chiroptonyssus robustipes was recorded for the first time on Molossus currentium (Mammalia, Chiroptera), corresponding to the first interspecific associations recorded for the species. An expansion in the occurrence of these ectoparasites in insectivorous bats in RS was observed. Furthermore, this is the first report of Rhipicephalus microplus parasitizing bats. Molecular research was carried out to investigate the presence of Rickettsia spp. and Trypanosoma spp. in animal carcasses. The investigation extended to Chiroptonyssus robustipes mites, which were tested for Rickettsia spp., Trypanosoma spp. and Leishmania spp. No mites or animals positive for the agents studied were found. Given the lack of established protocols for extracting DNA from C. robustipes, tests were conducted using three commercial kits and different protocols. The results indicated that the DNeasy Blood & Tissue Kit (GmbH, Qiagen®, Germany) was more effective in extracting total DNA (p < 0.05) when extracting the genetic material from just one whole mite, demonstrating higher concentrations of DNA in all tested groups. This study contributes not only to the understanding of parasitic diversity in bats, but also to the understanding of the interaction between these arthropods, hosts and potential pathogen transmission.